2010
DOI: 10.4314/acsj.v17i2.54203
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variability in sesame mutant lines in Kenya

Abstract: Sesame (Sesamum indicum L) is one of the major oil crops with potential for production by small-scale holders in the marginal agro-ecological zones of Kenya. Variability studies on yield and yield components of sesame mutant lines now in M7generation was carried out in two locations for two seasons in Kenya. The objective of the study was to assess performance of the mutant lines developed through induced mutational breeding. According to mean performance, the thirty selected mutant lines and four check cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
3
8
0
Order By: Relevance
“…Similar result was found by Daniya et al [22]. In the contrary, [23] found in significant positive correlation of oil content with seed yield and suggested that selection for oil content had no any effect on seed yield.…”
Section: Correlation Coefficientsupporting
confidence: 88%
“…Similar result was found by Daniya et al [22]. In the contrary, [23] found in significant positive correlation of oil content with seed yield and suggested that selection for oil content had no any effect on seed yield.…”
Section: Correlation Coefficientsupporting
confidence: 88%
“…Using breeding and selection approaches, over 38,000 genetic lines have been developed (United States Department of Agriculture, 2010). Cultivars are distinguished by capsule numbers per node; locule numbers within a capsule; stem branching patterns; seed shapes and colors; flower colors; leaf margin shapes; plant height; trichomes on the fruit, stem, and leaf; fruit maturation; and more [62] , [63] , [64] ; however, many cultivars are difficult to distinguish using these morphological characters. If the cp SSR information is compiled, these SSR loci can provide useful identification tools for some of these cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Saturated fatty acids present are palmitic and stearic acids making about 13%. The unsaturated fatty acids being the main constituents in sesame oil have also been extensively reported by many co-workers [7][8][9][10]37,38 3.2. Reaction Mechanism for Trans-esterification and Synthesis of the SEFAMESO Surfactant.…”
Section: Resultsmentioning
confidence: 90%